PENGARUH BULLYING TERHADAP KESEHATAN MENTAL SISWA SEKOLAH DASAR - Agustina; Pratiwi Pujiastuti; Ali Mustadi (Institut Pendidikan dan Bahasa Invada, 2023)
Education is the process of changing the attitudes and behavior of a person or group of people to mature humans through teaching and training. The purpose of this study was to determine the effect of bullying on the mental health of fourth-grade students at SDK Ende 3 Ende. This type of quantitative research. The sample in this study was 30 students in class IV. This study uses Pearson Correlation Product Moment analysis using the SPSS 25 application to measure the closeness of a linear relationship between two variables that have normal data distribution. Bullying has a positive and significant correlation with mental health (R) which is positive (0.718) and the account of the bullying act variable (0.615) > ttable corresponds to a significant level of 5% (2.006). The results of this study indicate that bullying greatly affects children's mental health. So it can be concluded that bullying has a positive and significant effect on mental health. The contribution of bullying to mental health can be seen through its determination coefficient (r2), which is 0.615. Bullying contributes 51.6% to mental development. A Contribution of 48.6% to mental development is obtained from other factors.